2015
DOI: 10.1039/c5nj00807g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsymmetrical 5,6-POCOP′-type pincer complexes of nickel(ii): impact of nickelacycle size on structures and spectroscopic properties

Abstract: Different structures and reactivities have been observed with the unsymmetrical pincertype complex (5,6-POCOP´)Ni(II)Br and its various derivatives compared to their analogous symmetrical 5,5-POCOP systems, thus serving to establish the importance of the size and degree of flexibility in the metallacycle rings. AbstractThis report describes the synthesis and characterization of a family of unsymmetrical pincer complexes of nickel(II) featuring both 5-and 6-membered nickelacycles. The room temperature reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…To access mononuclear POCOP pincer complexes of the type {2,6-(R 2 PO) 2 -R′ n -C 6 H 3– n }­NiX (X = Cl, Br), several different synthetic protocols have been developed, one of which involves refluxing the POCOP pincer ligand with NiX 2 in toluene . The cyclometalation reaction may be improved by replacing NiX 2 with a more soluble Ni­(II) source, adding a base to neutralize the byproduct HX, or using the combination of both strategies . Chloride complexes {2,6-(R 2 PO) 2 -R′ n -C 6 H 3– n }­NiCl can alternatively be synthesized by simply heating a mixture of resorcinol (or a substituted resorcinol), R 2 PCl, and nickel powder, as demonstrated by the Zargarian group …”
Section: Resultsmentioning
confidence: 99%
“…To access mononuclear POCOP pincer complexes of the type {2,6-(R 2 PO) 2 -R′ n -C 6 H 3– n }­NiX (X = Cl, Br), several different synthetic protocols have been developed, one of which involves refluxing the POCOP pincer ligand with NiX 2 in toluene . The cyclometalation reaction may be improved by replacing NiX 2 with a more soluble Ni­(II) source, adding a base to neutralize the byproduct HX, or using the combination of both strategies . Chloride complexes {2,6-(R 2 PO) 2 -R′ n -C 6 H 3– n }­NiCl can alternatively be synthesized by simply heating a mixture of resorcinol (or a substituted resorcinol), R 2 PCl, and nickel powder, as demonstrated by the Zargarian group …”
Section: Resultsmentioning
confidence: 99%
“…For the alkyl, ÀOSiR, ÀCF 3 , ÀN 3 and hydride substituents, a more direct approach can be used by reacting Grignard reagents, Me 3 SiL (L¼ÀOK, ÀCF 3 , ÀN 3 ) and LiAlH 4 , respectively, directly with the nickel halide [60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…A search of the literature revealed that most cyclonickelated complexes accessible via C–H nickelation are stabilized by pincer-type ligands . Our experience with the facile C–H nickelation of POCOP-type pincer ligands featuring aryl and alkyl phosphinite donor moieties encouraged us to test the reactivities of substrates bearing a single phosphinite DG. Initial tests showed that alkyl phosphinites were insufficiently reactive, whereas aryl phosphinites underwent relatively facile C–H nickelation.…”
Section: Introductionmentioning
confidence: 99%